Impact of online support of physical activity management using a wearable device on renal function in patients with acute coronary syndrome: a randomized controlled trial protocol - Toshimi Sato; Daisuke Suzuki; Yuichiro Sasamoto; Masahiro Ono; Namiko Shishito; Kohko Kanazawa; Akihito Watanabe; Koichi Naito; Shinichiro Morishita; Masahiro Kohzuki (PeerJ)
Background Acute coronary syndromes (ACS) often cause rapid decline in renal and cardiac function. In patients with ACS, combined renal dysfunction is associated with increased overall mortality and cardiovascular events. Physical activity (PA) management may crucially contribute towards protection of renal function in patients with ACS. This article describes the study protocol of a randomized controlled trial (RCT) assessing whether online support for PA management using wearable devices and information communication technology for patients with ACS facing difficulties in participating in outpatient cardiac rehabilitation after discharge can protect renal function following disease onset. Methods We have designed a two-arm RCT with a 3-month follow-up period. The online support intervention incorporates monitoring of PA, pulse rate, and blood pressure using a wearable device with an accelerometer and a web application system, as well as periodic educational feedback and goal setting. The primary study endpoint is the estimated glomerular filtration rate based on serum cystatin C (eGFRcys). The intervention effect will be assessed using the eGFRcys at 3 months adjusted for baseline values. The secondary endpoints are the urine albumin/creatinine ratio, brain natriuretic peptide levels, average step count, peak oxygen uptake, quality of life, and incidence of adverse events. Discussion This RCT will provide evidence regarding the effectiveness of online support for PA management as a renal protection strategy following ACS onset. This novel strategy not only mitigates barriers impeding participation in outpatient cardiac rehabilitation and protects cardiac and renal function in patients with ACS, but also may contribute towards improving survival and recurrence rates, preventing dialysis, and reducing medical and long-term care costs. Trial registration: The trial was registered in the Japan Registry of Clinical Trials on July 5, 2024. The registration number is jRCT1022240014 (Impact of Online Support of Physical Activity Management Using a Wearable Device on Renal Function in Patients with Acute Coronary Syndrome).